Molecular and phenotypic evaluation of wheat (Triticum aestivum) containing different combinations of rust resistance genes. (23rd March 2021) - Maré, Ansori; Boshoff, Willem H. P.; Herselman, Liezel
Abstract: Leaf, stem and stripe rust caused by Puccinia triticina, P. graminis f. sp. tritici and P. striiformis f. sp. tritici, respectively, are common wheat diseases. The deployment of complex rust resistance sources is likely to contribute to their durability. In this study, wheat varieties and experimental plants (F2 ), with different rust resistance gene combinations, were characterised using molecular markers, phenotypic evaluation and quantification of fungal biomass accumulation. The experimental wheat plants were developed from six donor parental varieties that in combination carry seven known rust resistance genes/quantitative trait loci (QTL). A timeline study revealed that quantification of fungal biomass accumulation for the rusts, 10‐day postinoculation (dpi), can successfully distinguish between resistant and susceptible wheat varieties. Phenotypic evaluation included seedling infection types and adult‐plant response types that were determined 15 dpi. Data obtained from the three methods were in support of each other and in combination successfully distinguished between rust‐resistant and susceptible experimental wheat plants. Resistance genes/QTL evaluated in this study, when deployed in combination, may lower the risk of rust outbreaks.